Job Satisfaction and Employee Loyalty as Performance Determinants - Yayat Sudrajat; Dodi Siswanto (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study aims to analyze the influence of job satisfaction and employee loyalty on the performance of general department employees at Pamanukan Medical Center Hospital. The background of the study is based on the importance of psychological factors and employee engagement in improving the effectiveness and quality of services, especially in the health sector which demands professionalism, accuracy, and high responsibility. The study used a quantitative approach with a survey method by distributing questionnaires to 68 active general department employees of the hospital. Data were analyzed using descriptive and inferential statistics, including validity and reliability tests, multiple linear regression, and t-tests and F-tests with the help of SPSS software version 22. The results of the study indicate that job satisfaction and employee loyalty have a positive and significant effect on performance, both partially and simultaneously, with a high level of contribution. This finding confirms that satisfaction and loyalty are key factors in shaping optimal employee performance in a public service-based work environment. Theoretically, this study strengthens the model of the relationship between affective and normative factors in employee performance, while practically providing implications for hospital management in designing policies oriented towards improving psychological well-being and employee engagement to support organizational productivity and sustainability.